Impact of timing of atrial fibrillation, CHA2DS2-VASc score and cancer therapeutics on mortality in oncology patients. Issue 2 (26th November 2020) - Hussain, Muzna; Misbah, Rabel; Donnellan, Eoin; Alkharabsheh, Saqer; Hou, Yuan; Cheng, Feixiong; Crookshanks, Michael; Watson, Chris J; Toth, Andrew J; Houghtaling, Penny; Moudgil, Rohit; Budd, G Thomas; et al.
Abstract : Objectives: To investigate timing and age distribution of atrial fibrillation (AF) in selected oncology patients, and the impact of AF timing, CHA2 DS2 -VASc score and cancer therapeutics on mortality. Methods: This is a retrospective cohort study of oncology patients referred to the cardio-oncology service from 2011 to 2018 for echocardiographic cardiosurveillance and/or pre-existing cardiovascular risk factor/disease management. Rates of first AF diagnosis was assessed using a parametric multiphase hazard model (predictive modelling) and non-parametrically by Kaplan-Meier with transformations tested using a bootstrap methodology. Results: Among 6754 patients identified, 174 patients had their first AF diagnosis before cancer while 609 patients had their first diagnosis of AF after cancer. Most first AF diagnosis occurred at/early after cancer diagnosis. Increasing AF prevalence at time of cancer diagnosis was seen across older age groups ranges. Diagnosis of cancer at an older age and exposure to cardiotoxic treatment (anthracyclines, HER2-neu inhibitors, tyrosine kinase inhibitors including ibrutinib and radiation) were associated with an increased risk of AF. Modelling of the hazard function of AF identified a high left-skewed peak within 3 years after cancer diagnosis ('early phase'), followed by a gradual late slight rise 3 years after cancer diagnosis ('late phase'). AF diagnosis was only associated with death in the early phase (p<0.001), while CHA2 DS2 -VASc score was only associated with death in the late phase (p<0.001). Conclusions: This study reports a nuanced/complex relationship between AF and cancer. First diagnosis of AF in patients with cancer was more common at/early after cancer diagnosis, especially in older patients and those exposed to cardiotoxic treatment. Pre-existing AF or a diagnosis of AF within 3 years after cancer diagnosis carried a negative prognosis. CHA2 DS2 -VASc score did not relate to mortality in those that developed AF within 3 years of cancer diagnosis.